Learning Through School Science Investigation Teachers Putting Research into Practice - Moeed, Azra (Springer Singapore, 2018)
This book explores teaching and learning through science investigation and practical work. It draws upon two representative case studies from New Zealand and examines what students are learning from science investigation; in addition, it identifies and describes ways in which teachers can make changes that benefit student learning when given time to reflect and respond to research literature and findings. The book illustrates how teaching through science investigations in ways that are informed by research can lead to positive learning outcomes for students. As such, it offers valuable insights for practitioners, researchers, and educators with an interest in learning through science investigation.